2001
DOI: 10.1083/jcb.200102093
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibition of the APC/C in HeLa cells is mediated by a complex of BUBR1, BUB3, CDC20, and MAD2

Abstract: The mitotic checkpoint prevents cells with unaligned chromosomes from prematurely exiting mitosis by inhibiting the anaphase-promoting complex/cyclosome (APC/C) from targeting key proteins for ubiquitin-mediated proteolysis. We have examined the mechanism by which the checkpoint inhibits the APC/C by purifying an APC/C inhibitory factor from HeLa cells. We call this factor the mitotic checkpoint complex (MCC) as it consists of hBUBR1, hBUB3, CDC20, and MAD2 checkpoint proteins in near equal stoichiometry. MCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
856
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 827 publications
(893 citation statements)
references
References 48 publications
31
856
1
5
Order By: Relevance
“…In support of this hypothesis, BubR1 has recently been shown to bind Cdc20 and inhibit the APC/C from ubiqutinating cyclin B, independent of Mad2 [Fang, 2002;Tang et al, 2001]. There is some in vitro biochemical evidence, however, that Mad2 and BubR1 act synergistically to inhibit Cdc20 [Fang, 2002;Sudakin et al, 2001;Tang et al, 2001]. Our studies show that either Mad2⌬C or GST-Mad1F10 can overcome the checkpoint in nocodazole-treated PtK1 cells where kinetochores lack both tension as well as attached microtubules.…”
Section: Comments and Conclusionsupporting
confidence: 75%
“…In support of this hypothesis, BubR1 has recently been shown to bind Cdc20 and inhibit the APC/C from ubiqutinating cyclin B, independent of Mad2 [Fang, 2002;Tang et al, 2001]. There is some in vitro biochemical evidence, however, that Mad2 and BubR1 act synergistically to inhibit Cdc20 [Fang, 2002;Sudakin et al, 2001;Tang et al, 2001]. Our studies show that either Mad2⌬C or GST-Mad1F10 can overcome the checkpoint in nocodazole-treated PtK1 cells where kinetochores lack both tension as well as attached microtubules.…”
Section: Comments and Conclusionsupporting
confidence: 75%
“…The spindle assembly checkpoint plays an essential role in maintaining genome integrity by Aurora-A induces mammary tumor formation X Wang et al holding cells with unaligned chromosomes at metaphase (Amon, 1999;Yoon et al, 2002;Andreassen et al, 2003). Mad2 selectively binds to unattached kinetochores and is capable of inhibiting anaphase-promoting complex (APC) activity (Sudakin et al, 2001;Tang et al, 2001;Fang, 2002). It was recently shown that overexpression of Aurora-A abrogates function of Mad2 in inhibiting APC, leading to the failure of the spindle assembly checkpoint (Anand et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bub1p binds to Bub3p throughout the cell cycle [reviewed in [Howell et al, 2000[Howell et al, , 2004Shah et al, 2004]. The association of SAC proteins with kinetochores is important for SAC function [Kadura et al, 2005;Taylor et al, 1998;Vanoosthuyse et al, 2004] perhaps because it alters the binding interactions between SAC proteins and influences the formation of the mitotic checkpoint complex (MCC) [Sudakin et al, 2001], which imposes a cell cycle arrest by binding to the Anaphase Promoting Complex (APC). The APC/C is a multi-protein ubiquitin ligase that targets important cell cycle proteins for degradation by the 26S proteasome.…”
Section: A Consensus Model For Spindle Checkpoint Functionmentioning
confidence: 99%